1983
DOI: 10.1073/pnas.80.8.2400
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin-immunoreactive neurons in rat and monkey cerebral cortex make symmetric synapses and have intimate associations with blood vessels.

Abstract: Neurons displaying cholecystokinin-like immunoreactivity (CCK neurons) in rat and monkey cerebral cortex were examined by light and electron microscopic immunocytochemistry. CCK neurons were found to be mainly bipolar cells present in all layers and in all areas of the rat cerebral cortex. CCK neurons were also found in all regions examined in monkey cortex (preand post-central gyri and superior parietal lobule). The somata and the dendritic processes of CCK neurons receive relatively few synapses but both sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…There seems to be general agreement that the CCK-, CRF-, and VIP-positive cells occur mainly in the supragranular layers in the rat and cat visual cortex (McDonald et al, 1982b, c;Merchenthaler et al, 1982;Hendry et al, 1983a;Peters et al, 1983;Swanson et al, 1983;Connor and Peters, 1984;Magistretti et al, 1984;Merchenthaler, 1984;Morrison et al, 1984;Magistretti and Morrison, 1985). It seems that the distribution of CRF-positive neurons is somewhat more widespread in the rat than the cat visual cortex, since a number of CRF-positive neurons have been reported outside layers I-II in the rat.…”
Section: Datrlbution Of Peptlde-contaming Neuronsmentioning
confidence: 97%
See 1 more Smart Citation
“…There seems to be general agreement that the CCK-, CRF-, and VIP-positive cells occur mainly in the supragranular layers in the rat and cat visual cortex (McDonald et al, 1982b, c;Merchenthaler et al, 1982;Hendry et al, 1983a;Peters et al, 1983;Swanson et al, 1983;Connor and Peters, 1984;Magistretti et al, 1984;Merchenthaler, 1984;Morrison et al, 1984;Magistretti and Morrison, 1985). It seems that the distribution of CRF-positive neurons is somewhat more widespread in the rat than the cat visual cortex, since a number of CRF-positive neurons have been reported outside layers I-II in the rat.…”
Section: Datrlbution Of Peptlde-contaming Neuronsmentioning
confidence: 97%
“…VIP-containing bipolar neurons constitute the main group ofpeptide-positive cells, which do not contain GAD. In addition, a small subset of CCK-positive bipolar cells can also belong to this group (Hendry et al, 1983a). These 2 groups of bipolars share the common feature of making synaptic contact with blood vessels, as well as with other cortical cells.…”
Section: Datrlbution Of Peptlde-contaming Neuronsmentioning
confidence: 99%
“…Therefore, these biologically active substances may not be involved in generation of the depolarizing response in the rabbit basilar artery. Peptides-containing nerves are also located in cerebral arteries (HENDRY et al, 1983), and transmission from these nerves to the smooth muscle cannot be blocked by the above-mentioned agents. The T.…”
Section: Discussionmentioning
confidence: 99%
“…Unequivocal evidence at the ultrastructural level indicates the intimate apposition, and in some cases the presence of true synapses, between neurotransmittercontaining profiles and intraparenchymal brain capil laries. In particular this has been demonstrated for VIP [10,11], acetylcholine [10], cholecystokinin [12,13] and NA [14,15]. In addition, pharmacological studies have demonstrated the presence of receptors for NA and VIP, coupled to cAMP-generating systems [16][17][18] in intra parenchymal microvessel preparations.…”
Section: Introductionmentioning
confidence: 97%